The Effects of Staff-rotation in Public Administration on the Decision to Bribe or be Bribed - Miloš Fišar; Ondřej Krčál; Rostislav Staněk; Jiří Špalek (Masaryk University, Faculty of Economics and Administration, 2019)
Periodic rotation of staff in public administration may lead to lower corruption, as it disrupts long-term relationships between public officials and potential bribers. This paper proposes an~experimental design that tests the~anti-corruption effect of staff rotation in situations where public officials have committed to reciprocating bribes. We find that staff rotation does not influence the~proportion of firms offering bribes but does reduce the~share of bribe acceptance and inefficient decisions owing to bribery. The~outcome of the~staff-rotation treatment, in which firms offered bribes even though they were rarely accepted by officials, is consistent with the~game having a~quantal response equilibrium
Keywords: D73; D81; 330; bribery; economic experiment; anti-corruption; staff rotation; corruption